Praha - with Czech translations by Marzia Paton (Mingling Voices, 2011)
Prompted by renowned poet E.D. Blodgett's deep love for and intimate experience of Prague, Praha is a poetic homage to the legendary city's vital spirit. As they build on one another, the poems in the collection lift the reader over the threshold of purely mythic understanding and into the heart of one of Europe's loveliest and most venerable cities. Each poem is accompanied by a translation into Czech, encouraging even those who do not know the language to immerse themselves in its sound. Superbly complemented by the mysteriously eloquent paintings of Czech artist Robert Kessner, Praha offers the moods of Prague in its many seasons and in all its magic.